Implementasi Hak Atas Upah Pekerja Oleh Perusahaan Berdasarkan Undang-Undang Nomor 13 Tahun 2003 - Mustakim, Mustakim (Indo Publishing, 2025)
This study aims to analyze the implementation of workers' rights to wages by companies based on Law No. 13 of 2003, whereby the minimum wage is in accordance with the regional minimum wage (UMR). The study uses a qualitative descriptive method with data collection techniques through interviews. The results show that companies have implemented work and wage systems that are in accordance with the principles of industrial relations, where workers receive fair wages, on time, and without inappropriate deductions. However, the data shows that cases of industrial relations disputes in Indonesia in the last five years from 2020 to 2024 are still quite high. This condition indicates weak government supervision as one of the main parties in the industrial relations system. The government needs to strengthen its supervisory and guidance functions towards companies so that industrial relations principles can be implemented comprehensively and consistently.